2019
DOI: 10.1017/dsi.2019.23
|View full text |Cite
|
Sign up to set email alerts
|

Observations on the Effects of Skill Transfer through Experience Sharing and In-Person Communication

Abstract: An essential part of any space in which physical prototyping and prototype-driven product development is being conducted is the education of its users in the necessary skills to fully utilise the material resources of the space. This paper describes how two different skills were transferred between five projects in our research laboratory, TrollLABS. Based on the observed skill-transfers in the production of PCBs and use of RF-communication in mechatronics projects certain tendencies emerged: How the use of fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…AI systems like ChatGPT are designed to iterate and refine their outputs based on feedback loops that often prioritize reinforcing successful outcomes, the exact mechanism that can make ChatGPT hallucinate. In contrast to experienced human designers who might draw on implicit, skill-based knowledge (Vestad et al, 2019) and past experiences to consider multiple solutions, ChatGPT exhibits a form of 'design fixation,' a trait often observed in novice engineering students who might latch onto their first successful design due to limited experience (Purcell and Gero, 1996). This tendency also illustrates a known limitation of AI in dealing with resistance or setbacks.…”
Section: Discussionmentioning
confidence: 99%
“…AI systems like ChatGPT are designed to iterate and refine their outputs based on feedback loops that often prioritize reinforcing successful outcomes, the exact mechanism that can make ChatGPT hallucinate. In contrast to experienced human designers who might draw on implicit, skill-based knowledge (Vestad et al, 2019) and past experiences to consider multiple solutions, ChatGPT exhibits a form of 'design fixation,' a trait often observed in novice engineering students who might latch onto their first successful design due to limited experience (Purcell and Gero, 1996). This tendency also illustrates a known limitation of AI in dealing with resistance or setbacks.…”
Section: Discussionmentioning
confidence: 99%
“…Typical design creativity studies focus on a shorter time span or do not account for the genealogy of ideas and prototypes. Recent studies have shown that the genealogy of ideas is essential for successful solutions, and the genealogy of prototypes is essential for effective design thinking (Vestad et al, 2019). Furthermore, the stage of development criterion also tackles the issue of design creativity, as the stage of an idea and its prototyping are related.…”
Section: Discussionmentioning
confidence: 99%
“…They promote creativity and enhancement of technical and creative skills of students and professionals (Hilton et al, 2020;Rieken et al, 2019), and are expected to facilitate greater agility and add value in the early stages of engineering design (B€ ohmer et al, 2015;Jensen and Steinert, 2020). Though several studies categorize and differentiate makerspaces on the basis of such as available machinery and equipment (Jensen et al, 2016;Wilczynski andHoover, 2017), users (O'Connell, 2017), business models (Schaffers et al, 2007), self-reported token based activity monitoring (Gourlet and Dass� e, 2017), and management strategies (Tomko et al, 2021), there is a distinct lack of empirical data on actual usage, activities and social interactions in makerspaces, although this is generally regarded a distinctive trait of these spaces (Vestad et al, 2019).…”
Section: Literature Reviewmentioning
confidence: 99%